Hemophilia A Complicated by Ulcerative Colitis - Maxim Olivier; Mario Madruga; S. J. Carlan; Li Ge (Case Reports in Gastrointestinal Medicine)
Background. Hemophilia A is an X-linked recessive disorder characterized by defective synthesis of Factor VIII protein. Depending on the level of FVIII activity, patients may present with easy bruising, inadequate clotting of traumatic or mild injury, or in severe hemophilia, spontaneous hemorrhage. Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) that is reported to have a decreased frequency of occurrence in subjects with coagulation disorders. Case. A 26-year-old white male with Hemophilia A was admitted for one month of rectal bleeding. The bleeding continued despite Factor VIII replacement and colonoscopy and biopsy were performed confirming the presence of active UC. Conclusion. Ulcerative colitis with underlying F VIII deficiency can result in serious, prolonged, and possibly fatal bleeding if left unrecognized and untreated. Treatment of both conditions concurrently utilizing tertiary facilities and consultations appears to be the safest strategy for management.